Hyperthyroidism with concurrent thyroid cancer - RULLI, F.; ZANELLA, E.; FARINON, A.M.; SIANESI, M.; SCIACCHITANO, S.; DANESE, D.; PONTECORVI, A. (Annali Italiani di Chirurgia, 2001)
The occurrence of thyroid malignancy is considered a rare event in hyperthyroid patients. With the aim of assessing the clinical relevance of this association, we have analyzed the incidence of thyroid cancer in hyperthyroid patients treated by surgery. The incidence of thyroid cancer was retrospectively evaluated in 202 hyperthyroid patients who underwent thyroidectomy during a twenty-year period. A thyroid cancer was diagnosed in 12 cases (5.9 per cent). Histologic examination revealed the presence of papillary carcinoma in 9 cases, follicular carcinoma in 1 case and Hürthle cell carcinoma in 2 cases. The association between thyroid cancer and hyperthyroidism was more frequent in toxic adenomas (17.8 per cent) than in toxic diffuse (5.3 per cent) or multinodular goiters (1.7 per cent). In 8 patients they presented as an occult carcinoma (maximum diameter below 1 cm), but unfavourable histologic features, such as local invasiveness and multifocality, were found in 5 of them. Follow-up data indicate that all 12 patients are currently alive and apparently free of disease. Hyperthyroid patients, particularly those affected by toxic adenomas, should be carefully evaluated to exclude the presence of concurrent malignancy. A special attention should be made moreover to the presence of “occult” lesions that, in our study was characterized in a higher proportion (62.5 per cent) of cases, by unfavourable histologic features.